Provings—Planning and protocol - Nagpaul, V.M. (British Homeopathic Journal, 1987)
Provings provide knowledge about the instruments that we, as homœopaths, use in combating human sickness.A vast amount of pre-planning and laying of protocols is necessary in conducting the provings for the purposes of achieving scientific validity of the work. The author has therefore dwelt only upon various stages of planning and protocols necessary in conducting successful provings.